Novas fontes de resistência em meloeiro a Liriomyza sativae, Acidovorax avenae e Alternaria spp. - Costa, Jose Maria da (Universidade Federal Rural do Semi-Árido, 2017)
The objective of the present work was to identify sources of resistance in melon accessions to Liriomyza sativae; Alternaria spp., and Acidovorax avenae. Two experiments were performed in a greenhouse and in the Laboratory of Applied Entomology (UFERSA) in a completely randomized design, with ten replicates, each plant being a plot. In the first experiment 38 accessions and two hybridswere evaluated. The infestation was held in cages coated with antiophidic screen. The second experiment was performed with the accessions that revealed to be promising and some were susceptible in the first trial. In the evaluations, the number of mines, larvae, pulps and adult flies were determined. In some materials, leaf colorimetry, number, size of stomata and trichomes were analyzed. The accessions AM 55 and Nantais Oblong as well as the Ruthenium hybrid are resistant to Liriomyza sativa. The number of mines, larvae and adult flies correlated negatively with the number of trichomes and positively with the size of the stomata. Regarding the Alternaria leaf blight, fifty-eight accessions were initially evaluated in a randomized block design (DBC) with three replications under field conditions. In a second experiment, twelve accessions were also evaluated under field conditions, in both tests the evaluations were accomplished 50 days after the transplanting, as far as the severity and incidence of plants with Alternaria. It was concluded that there is variability in the germplasm of melon for reaction to the Alternaria leaf blight, being the accessions C-AC-04, C-AC-08, C-AC-26, C-AC-31, I 162, I 173 e MR-1 with lower severity averages and incidence of diseased plants, being evaluated as promising for use in breeding programs of melon for resistance to the pathogen. For the reaction to A. avenae, fifty accessions were evaluated in greenhouse and in field conditions. There has been accomplished inoculations with bacterial suspension in the concentration os 1,0 x 108 UFC ml-1. There were evaluated leaves (in a controlled environment), leaves and fruits (in field) with bacteriose symptoms. The C-AC-12 accession has intermediate resistance Acidovorax avenae
New sources of resistance in melon to Liriomyza sativae, Acidovorax avenae and Alternaria spp.
Keywords: Cucumis melo; Liriomyza sativae; Mancha de alternaria; Mancha aquosa; Germoplasma; Cucumis melo; Liriomyza sativae; Alternaria leaf blight; Fruit blotch; Germplasm; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA